Cerebral correlates of disturbed executive function and memory in survivors of severe closed head injury: a SPECT study. Issue 5 (May 1992) - Goldenberg, G; Oder, W; Spatt, J; Podreka, I
Abstract : Thirty six patients in the chronic stage after severe closed head injury were examined with tests of executive function, memory, intelligence, and functional capacities in daily living. Correlations were sought between test results and Tc-99m-HMPAO uptake of frontal, temporal, and thalamic regions assessed by SPECT. Neither the number of significant correlation coefficients between memory tests and regional uptake nor that between temporal uptake and tests exceeded chance. For the remaining tests, correlations to thalamic regions were stronger than those to the frontal regions, and those to right brain regions stronger than those to homologous left brain regions. Relationships of thalamic isotope uptake to neuropsychological performance may reflect the impact of diffuse brain damage and particularly of diffuse axonal injury on mental capacities.